Six-month evaluation of novel bioabsorbable scaffolds composed of poly-L-lactic acid and amorphous calcium phosphate nanoparticles in porcine coronary arteries. (August 2018) - Dinh Nguyen, Thanh; Feng, Gaoke; Yi, Xin; Lyu, Yongnan; Lan, Zhiyuan; Xia, Jinggang; Wu, Tim; Jiang, Xuejun
Objective: Using coronary angiography and intravascular ultrasound methods to evaluate the performance of the novel fully bioabsorbable scaffold (NFBS) composed of poly-L-lactic acid/amorphous calcium phosphate (PLLA/ACP) at six-month follow-up by comparing with PLLA scaffolds Methods: Twelve PLLA/ACP scaffolds and 12 PLLA scaffolds were implanted into the coronary arteries of 12 miniature pigs. Quantitative coronary angiography (QCA) was used to measure the reference vessel diameter (RVD), mean lumen diameter (MLD) and late lumen loss (LLL). According to IVUS images, we calculated the strut malapposition rate (SMR) at post implantation, strut overlap rate (SOR), reference vessel area (RVA), mean stent area (MSA), mean lumen area (MLA) and luminal patency rate (LPR) at six-month follow-up. The radial strength of the scaffold was evaluated using a catheter tensile testing machine. Results: QCA results indicated that, at six month, MLD of PLLA/ACP scaffolds was greater than those of PLLA scaffolds (2.47 ± 0.22 mm vs. 2.08 ± 0.25 mm, P < 0.05); LLL of PLLA/ACP scaffolds was less than those of PLLA scaffolds (0.42 ± 0.20 mm vs. 0.75 ± 0.22 mm, P < 0.05). IVUS results showed the SMR and SOR were all significantly less with the PLLA/ACP scaffolds than the PLLA scaffolds (5.84% ± 3.56% vs. 17.72% ± 4.86%, P < 0.05) (6.17% ± 4.63% vs. 17.65% ± 4.29%, P < 0.05). MSA, MLA and LPR of the PLLA/ACP scaffolds were all greater than those of PLLA scaffolds (6.35 ± 0.45 mm 2 vs. 5.35 ± 0.51 mm 2, P < 0.05) (4.76 ± 0.46 mm 2 vs. 3.77 ± 0.46 mm 2, P < 0.05) (78.01% ± 12.29% vs. 61.69% ± 9.76%, P < 0.05). Radial strength of PLLA/ACP scaffold at six month was greater than that of PLLA scaffold (76.33 ± 3.14 N vs. 67.67 ± 3.63 N). Conclusion: The NFBS had less stent recoil, better lumen patency rate and greater radial strength than PLLA scaffolds. The results suggest the NFBS scaffolds can maintain the structural strength and functional performance, which are effective for up to six months when implanted in porcine coronary arteries.